Effects of irrigation and nitrogen levels on qualitative and nutritional aspects of fig-trees (Ficus carica L.) (Scientia Agricola, 1994)
In order to evaluate qualitative and nutritional aspects of fig-trees with respect to six irrigation and six nitrogen levels, at Ilha Solteira, SP, Brazil, an experiment was carried out in randomized blocks, with subdivided plots, and four replications. Results showed that in four dates during harvest, only the first analysis (January 2, 1991) showed influence of nitrogen fertilization on fruit soluble solids (brix). There was no significant effect of treatments on pulp/peel relation for the four harvestings. In relation to leaf macronutrient concentration at flowering, water supply influenced N, P and Ca concentrations, and nitrogen influenced only Ca concentration. For an average of 10 t.ha-1 of mature fruit and 1.3 t.ha-1 of immature fruit production, there was a nutrient export of about 65 kg.ha-1 of N; 10 kg.ha-1 of P2O5; 44 kg.ha-1 of K2O; 35 kg.ha-1 of Ca and 9 kg.ha-1 of Mg.